동종 조혈모세포이식술 후 안구건조증의 임상증상 및 징후 - 백진욱(Jin Uk Beak), 하민지(Min Ji Ha), 이로운(Rowoon Yi), 유영식(Young Sik Yoo), 김현승(Hyun Seung Kim), 나경선(Kyung-Sun Na) (Daihan angwa haghoi jabji, 2019)
목적: 동종 조혈모세포 이식 후 안구건조증환자의 증상 및 징후를 알아보고 이들 간의 상관관계를 분석하고자 하였다. 대상과 방법: 안구건조증이 동반된 동종 조혈모세포 이식환자 96명 중 96안을 대상으로 후향적 연구를 시행하였다. 동종 조혈모세포이식 전, 이식 후 1, 2, 4개월 후에 시력, 안압, 쉬르머검사 1, 눈물 오스몰 농도, 눈물막파괴시간, 안구 염색 점수 검사(Ocular Staining Score [OSS] Oxford)와 안구 표면 질환 지수(Ocular Surface Disease Index, OSDI)를 시행하였다. 결과: 이식 전후의 OSS와 OSDI의 변화가 유의한 양의 상관관계가 나타났다. 다른 지표들과 쉬르머검사값은 유의한 상관관계를 보이지 않았다. 남성에서 객관적 지표인 OSS가 주관적 지표인 OSDI보다 유의하게 높게 관찰되었다. 결론: 안구 이식편대숙주질환을 진단할 때 주관적인 증상만으로는 진단하기 어려울 때가 있다. 그러므로 이식 전 눈물막 상태와 안구표면 지표에 대한 기본값을 검사하여, 이식 후 안구 표면 변화에 대한 정기적인 평가를 시행해야 할 것으로 생각된다. Purpose: To identify the symptoms and signs of patients with dry eye disease (DED) after allogenic hematopoietic stem cell transplantation (HSCT) and analyze the correlations between these signs and symptoms. Methods: We performed a retrospective study in 96 eyes of HSCT recipients with DED. Visual acuity, intraocular pressure, Schirmer test 1 (with anesthesia), tear osmolarity, tear break-up time, Ocular staining score (OSS, Oxford), and Ocular staining disease index (OSDI) were examined before and 1, 2, and 4 months after HSCT. Results: A significant positive correlation was noted between changes in OSS and changes in OSDI. No ocular parameters showed significant correlations with Schirmer test values. Men more frequently described alleviation of symptoms greater than their objective results compared to women. Conclusions: Subjective symptoms alone may be insufficient when diagnosing ocular graft-versus-host disease. We recommend regular ophthalmologic examination after allo-HSCT. In addition, a baseline ocular profile of tear dynamics and ocular surface parameters should be conducted before allo-HSCT. KCI Citation Count: 0